Training on Creative Analysis of ANOVA Statistical Tests with SPSS Applications - Hidajat, Flavia Aurelia; Nurjannah, Nurjannah; Partasiwi, Nurashri; Sovia, Anny; Hidajat, Helga Graciani; Gani, Suriati Abdul (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2024)
Background: ANOVA analysis is crucial for comparing multiple population means and is highly beneficial for final-year students. However, many face challenges in mastering it due to the lengthy SPSS installation process and the complexity of ANOVA material. Despite its importance, ANOVA training is rarely conducted. This research aims to fill that gap. Contribution: This community service aims to provide creative training for participants regarding ANOVA analysis using SPSS applications technology. Method: Final-year students (semester 6 and above) participated in basic training using SPSS 22. Pre- and post-training evaluations measured effectiveness. Results: The evaluation results showed that 92% of participants from final year students experienced improvement in mastering ANOVA analysis. Conclusion: This activity successfully increased students' knowledge to master ANOVA analysis using SPSS 22 applications. Thus, it allows the emergence of various research topics that apply the ANOVA application so that research in the academic world becomes better.